2014
DOI: 10.1016/j.jped.2013.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Variables associated with extra uterine growth restriction in very low birth weight infants

Abstract: extrauterine growth restriction was high in the population, especially for SGA newborns and those with neonatal morbidities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
41
3
10

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 21 publications
4
41
3
10
Order By: Relevance
“…Lima et al 15 also found similar results for weight Z-scores. Embleton et al 48 reinforce the multiplicity of factors involved in the development of EUGR and associate the accumulation of nutritional deficits in the first weeks after birth to nutritional practices, resulting in EUGR.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Lima et al 15 also found similar results for weight Z-scores. Embleton et al 48 reinforce the multiplicity of factors involved in the development of EUGR and associate the accumulation of nutritional deficits in the first weeks after birth to nutritional practices, resulting in EUGR.…”
Section: Discussionsupporting
confidence: 53%
“…Although the American Academy of Pediatrics recommends that extrauterine growth rate should aim to equal intrauterine growth rate of a premature infant with same gestational age 2,29 , the postnatal growth curves seem more appropriate to follow their growth 37 , and currently, the Fenton & Kim 9 and Fenton et al 10 curves approach the standard for classifying and following newborns until the corrected age of 50 weeks 11 . Lima et al 15 also disagree with the American Academy of Pediatrics recommendations.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The characterization of the sample in relation to weight, gestational age (GA), IG/weight ratio and length of stay identified that most of the results to the very low Weight premature infants (VLWPT) were similar to VLWPT in other national and international studies 14,15 . The EGR, shown by the important fall on average of the Z score of three anthropometric variables of birth until hospital discharge, presented averages of Z score lower when compared to similar study 16 carried out in four neonatal units of Rio de Janeiro, Brazil, where 570 premature were analyzed using the same assessment of the growth curve, and there were 39.1% high EGR, in relation to weight.…”
Section: Discussionmentioning
confidence: 81%
“…Este estudo observou que a restrição do crescimento pós-natal ocorreu em 71% dos RNPT que apresentaram muito baixo peso ao nascer, enquanto ocorreu em 63 e 39% nos estudos de Gianini et al 34 e de Lima et al 35,36 . Embleton et al 37 demonstraram que a restrição do crescimento pós-natal está relacionada com a deficiência cumulativa da ingestão proteica e calórica observada até a quinta semana de vida.…”
Section: I S C U S S ã Ounclassified